Bannon brothers [large type] : honor - Dailey, Janet (Thorndike Press, 2012)
When two of her friends, thousands of miles apart, are struck down, Kenzie, an expert trainer of combat dogs, turns to Link Bannon, a high-level intelligence officer, for help in finding the truth-- a dangerous mission that puts them in the path of an unhinged killer.